Neuroendocrine adaptations to bariatric surgery. (15th December 2015) - Dixon, J.B.; Lambert, E.A.; Lambert, G.W.
Abstract: The global epidemic of obesity and its related disease in combination with robust physiological defence of intentional weight loss generates a pressing need for effective weight loss therapies. Bariatric surgery, which works very effectively at delivering substantial sustained weight loss, has been an enigma with respect to mechanism of action. Naive concepts of restriction and malabsorption do not explain the efficacy of the most commonly used bariatric procedures. This century has seen increased interest in unravelling the mystery of the mechanisms underlying surgery associated weight loss with a focus on integrative gastrointestinal (GI) physiology, gut–brain signalling, and beyond weight loss effects on metabolism. GI interventions, some very minor, can alter GI wall stretch and pressure receptors; a range of GI hormones affecting hunger and satiety; bile acid metabolism and signalling; the characteristics of GI microbiome; portal vein nutrient sensing; and circulating concentrations of amino acids. Understanding the mechanisms involved should present targets for less invasive effective therapies. Highlights: For 50 years we have known bariatric surgery generates sustained weight loss. Innovative surgeons refined human procedures in the operating room to improve safety and efficacy. It works – does the mechanism of action really matter? Restriction and malabsorption make sense. This century we the surgeons observations back to the bench and gaining knowledge about putative mechanisms.